ANALISIS POTENSI BANJIR DI SAWAH MENGGUNAKAN DATA MODIS DAN TRMM (STUDI KASUS KABUPATEN INDRAMAYU) (ANALYSIS OF POTENTIAL FLOOD IN PADDY FIELD USING MODIS AND TRMM DATA (CASE STUDY: INDRAMAYU DISTRICTS)) - Nur Domiri Febrianti; Dede Dirgahayu Domiri (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2012)
The occurrence of flooding in paddy field may cause the decrease of total production. To increase the food sufficiency within the country, the monitoring of flood affected paddy field is very important to be implemented. The satellite imagery is one of tools for monitoring the flooding area. In this study; we used remotely sensed data from MODIS (Moderate Resolution Imaging Spectroradiometer) and TRMM (Tropical Rainfall Measuring Mission) for January 2011 and January 2012, respectively. The district of Indramayu was selected as the study site due to one of the center of the rice production. The flood frequency method was utilized to estimate the flood duration. Some assumption used in this study, i.e.: (i) the assumed to be wetland rainfed rice. (ii) Rice fields are assumed in the flat.(iii) The rainfall exceeds the crop water demand will be potentially because the floods, (iv) The rainfall have large impact causing flooding when compare to index vegetation greenness. The calculation of the flood potential did known that the equation used compelling enough because it has been in accordance with actual flood events. The class of potential flooding were identifying as a class of height severe flooding. The calculation of flood frequency in January 2011 showed that there had been flooding up to 4 times a month. Besides, there is 18,400 ha that has four times frequency of flooding, respectively and requires to be aware crop failures occurred in both conditions. The condition on January 2012 was in a safe because floods occurred only one time. The extensive flooding of rice fields in Indramayu district January 2012. Key words : Flooded rice fields, Frecuency of flooding, MODIS, TRMM